Basic Concepts Viewed from Frontier in Inorganic Coordination Chemistry - Akitsu, Takashiro (IntechOpen, 2018)
This book is both a review of current research and an undergraduate textbook for inorganic chemistry at university level. In university undergraduate lectures, basic concepts are mainly explained and added examples of frontier research are optional. However, in many cases, frontier research is more interesting for students than basic studies. This book is aimed at undergraduates in inorganic chemistry. Each author introduces or reviews "frontier research topics" of inorganic coordination chemistry. Additionally, "basic concepts," as found in textbooks on this subject, indicate application examples of "frontier research topics."